THE EFFECT OF ADDITION PROBIOTIC IN FEED TO GROWTHAND SURVIVAL RATE OF CATFISH (Ompokhypopthalmus) USING BIOFLOCS SYSTEM ON PEAT SWAMP WATER - Meiza, Maharanny; Putra, Iskandar; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research aim to determine the optimal dose of additional probiotic EM4 in feed to the growth performance and survival rate of Catfish (Ompok hypopthalmus) by using biofloc system on peat swamp water. This research was conducted on 40 days from June,13to August 2, 2019 at Technical Service Unit (UPT) of Hatchery, Faculty of Fisheries and Marine, University of Riau. This research was using experimental method by completely random design (RAL) one factor with three replications. The treatments were: P1 (without EM4), P2 (EM4 10mL / kg of feed), P3 (EM4 15 mL / kg of feed), P4 (EM4 20mL / kg of feed). The material used probiotic EM4, molasses and peat water with a pH of 4. The results showed that a different doses of additional probiotic EM4 affecting the growth performance and the survival rate of catfish (Ompok hypophthalmus) usingbiofloc system on peat swamp water. In addition, it also affected the absolute weight growth, absolute length growth, feed efficiency and feed conversion ratio. The optimal dose was at 10 mL/kg of feed as it showed significantly different results compared to control and was not differ significantly at higher doses. So that while being applied in terms of economy, 10 mL/kg was the most efficient dose, by giving the an absolute growth of 8\.64 g, growth of an average length of 12.93 cm, the specific growth rate of 8.57%, the survival rate was 100%, feed efficiency was 120.4% and feed conversion ratio 0.8. Keywords: Probiotic, Catfish, biofloc, peat swamp water